Design and Characterization of In-Plane Piezoelectric Microactuators - Javier Toledo (Actuators, 2017)
In this paper, two different piezoelectric microactuator designs are studied. The corresponding devices were designed for optimal in-plane displacements and different high flexibilities, proven by electrical and optical characterization. Both actuators presented two dominant vibrational modes in the frequency range below 1 MHz: an out-of-plane bending and an in-plane extensional mode. Nevertheless, the latter mode is the only one that allows the use of the device as a modal in-plane actuator. Finite Element Method (FEM) simulations confirmed that the displacement per applied voltage was superior for the low-stiffness actuator, which was also verified through optical measurements in a quasi-static analysis, obtaining a displacement per volt of 0.22 and 0.13 nm/V for the low-stiffness and high-stiffness actuator, respectively. In addition, electrical measurements were performed using an impedance analyzer which, in combination with the optical characterization in resonance, allowed the determination of the electromechanical and stiffness coefficients. The low-stiffness actuator exhibited a stiffness coefficient of 5 × 104 N/m, thus being more suitable as a modal actuator than the high-stiffness actuator with a stiffness of 2.5 × 105 N/m.